KOUMISS THERAPY IN THE HOSPITALITY INDUSTRY - Шидловська, Олена; Арпуль, Оксана (SWorldJournal, 2025)
The article explores the therapeutic and preventive aspects of using kumis as a traditional functional food product. Its composition, nutritional value, and positive effects on the human body are described. The current state and prospects of kumis use in